Pendampingan Dalam Mengimplentasikan Strategi Branding Dan Pengemasan Untuk Meningkatkan Daya Saing Produk Sempol Ayam Di Desa Cibatu Cikarang Selatan - Ardana, Olivia; Rani Ronita Sinambela; Yulia Rahmawati; Shafira Putri Amir; Pupung Purnamasari (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This service journal highlights the efforts to develop the product packaging of chicken sempol in Sempol Ayam Wisnu micro-enterprise located in South Cikarang. This research was conducted using a qualitative approach, combining direct observation and interviews with MSME owners. This service program aims to improve the competitiveness of Sempol Ayam products in Cibatu Village, South Cikarang, by implementing effective branding and packaging strategies. Sempol Ayam micro-enterprise managed by Mr. Mustofa faces various challenges in terms of branding, packaging, and marketing, which have an impact on consumer perceptions and product positioning in an increasingly competitive market. Through qualitative methods involving in-depth observations and interviews, we identified an urgent need to improve the product's visual identity and packaging. The program included the development of a new attractive and memorable logo, as well as a tagline that reflects the product's values. In addition, we provided training on effective marketing strategies, including proper utilization of social media and promotional techniques, to expand market reach. The results of the program showed a significant increase in product appeal, selling points, and brand awareness among consumers. Hopefully, this strategy can empower Sempol Ayam MSMEs to continue to innovate, improve product quality, and ultimately contribute to the welfare of the local community. This program not only provides direct benefits to Pak Mustofa's business, but also serves as an inspiring example for other MSMEs in facing similar challenges in a competitive market